2014
DOI: 10.21767/amj.2014.2105
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-associated pneumonia

Abstract: BackgroundVentilator-associated pneumonia (VAP) is a type of nosocomial pneumonia that occurs in patients who receive mechanical ventilation (MV). According to the International Nosocomial Infection Control Consortium (INICC), the overall rate of VAP is 13.6 per 1,000 ventilator days. The incidence varies according to the patient group and hospital setting. The incidence of VAP ranges from 13-51 per 1,000 ventilation days. Early diagnosis of VAP with appropriate antibiotic therapy can reduce the emergence of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…All ICU nurses were female like the study of Micik et al [38] who stated that 90.9% of the participant were female. The present study elaborated that, more than half of the ICU nurse's were in the age group from (25)(26)(27)(28)(29) year old this result was in congruent with Kapucu et al [39] who emphasized that nearly half of the participant for preventing VAP were 25-29 years old. Regarding level of education present study showed that, majority of ICU nurses were BSN while only few were MSN.…”
Section: Socio Demographic Characteristic Among Icu Nurse's For Vap Prevention Measuressupporting
confidence: 89%
See 1 more Smart Citation
“…All ICU nurses were female like the study of Micik et al [38] who stated that 90.9% of the participant were female. The present study elaborated that, more than half of the ICU nurse's were in the age group from (25)(26)(27)(28)(29) year old this result was in congruent with Kapucu et al [39] who emphasized that nearly half of the participant for preventing VAP were 25-29 years old. Regarding level of education present study showed that, majority of ICU nurses were BSN while only few were MSN.…”
Section: Socio Demographic Characteristic Among Icu Nurse's For Vap Prevention Measuressupporting
confidence: 89%
“…On the other hand, the VAP is considered one of the most serious infection in the ICU, with the management of risk heavily depended on sincere efforts of the ICU nursing staff [9]. Hence, disseminating the necessary knowledge and explaining the proper protocol of applying the preventive measures of VAP are of utmost importance in order to achieve an appropriate level of adherence and computability among ICU-nursing staff [27]. It is important to apply an effective and productive methodology to realize the goal of teaching together with sustained learning [24].…”
Section: Problem Statementmentioning
confidence: 99%